Theoretical framework - Tosun, Jale; Kittel, Bernhard; Pauknerová, Daniela (Intergenerational transmission and economic self-sufficiency, 2021)
In this chapter, we outline the theoretical framework that guides the case studies presented in the Chapters 4-14. The empirical phenomenon, in which all contributions in this volume are collectively interested, is economic self-sufficiencyeconomic self-sufficiency as introduced in Chapter 1.